2020
DOI: 10.3390/healthcare8010050
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Swallowing Care on Safe Oral Intake Using Ultrasound-Based Observation of Residues in the Epiglottis Valley: A Pragmatic, Quasi-Experimental Study

Abstract: The demand for methods to ensure safe oral consumption of food and liquids in order to prevent aspiration pneumonia has increased over the last decade. This study investigated the safety of swallowing care selected by adding ultrasound-based observation, evaluated its efficacy, and determined effective content of selected swallowing care. The study employed a pragmatic quasi-experimental research design. Participants were 12 community-dwelling adult patients (age: 44–91 years) who had experienced choking withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Assessments also include differential diagnosis from dysphagia caused by organic causes such as pharyngeal tumors [ 38 40 ]. Since US provides an objective assessment of the motion of the hyoid bone and larynx and may help to detect NOD, it may be added to the current swallowing screening test for the more detailed management [ 41 , 42 ] of dysphagic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Assessments also include differential diagnosis from dysphagia caused by organic causes such as pharyngeal tumors [ 38 40 ]. Since US provides an objective assessment of the motion of the hyoid bone and larynx and may help to detect NOD, it may be added to the current swallowing screening test for the more detailed management [ 41 , 42 ] of dysphagic patients.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Nurses demonstrate that they belong in this category when they foresee and fix problems, prioritise care and competing demands, detect patterns and indications, all the while applying evidence to their assessments and care. 18 , 19 Organisations that support evidence‐based education, quality of care, and strive for improved patient outcomes are more likely to be in alignment with knowledge workers needs and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of perception of the importance of collaboration with physicians, nurses, and speech-languagehearing therapists in oral healthcare were lower in the dental students than in the nursing students. Physicians and nurses play the main roles in providing healthcare, including oral healthcare for patients in hospitals, older adult patients in long-term care facilities, and community-dwelling older adult patients [8][9][10][11][12][13][14][15]32]. Furthermore, nurses can also encourage patients to undergo dental treatments and receive care from oral health professionals [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have reported that oral healthcare is important in the prevention of viral infections, including COVID-19 infection [5][6][7]. Therefore, collaborative oral healthcare among health professionals is also important in preventing these diseases in patients in hospitals, older adults in long-term care facilities, and community dwelling older adults [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%